The curious case of linguistic rights silence in Singapore - Tang, Jerine Kit-Ling (2017)
This study calls into question the uncontroversial normalisation of the notions of language rights and linguistic justice as conceptual apparatuses in the scholarly discourse on the management of linguistic diversity. In highlighting the success of Singapore’s linguistic regime in spite of its silence on language rights, the paper examined the existing linguistic regime to explore how it lines up with the theoretical rights discourse to explicate the state’s orientation towards language rights. The study found that Singapore appeals to an alternative conceptual orientation to linguistic rights management that does not involve the recognition of rights. To investigate how the state-engineered multiculturalism and multilingualism in Singapore appears to sit comfortably with the citizenry, such that they reciprocate with a similar silence on language rights of their own, the language values and perception of language rights of the citizenry were examined. The results showed a congruence between Singaporeans’ linguistic values and perception of language rights recognition and the state’s linguistic regime, and analysed how this congruence was achieved. The study then discussed the implication of the success Singapore’s linguistic regime has on the existing language rights debate.